Implementation of the ABCDEF Bundle for Critically Ill ICU Patients During the COVID-19 Pandemic: A Multi-National 1-Day Point Prevalence Study - Liu, Keibun; Nakamura, Kensuke; Katsukawa, Hajime; Nydahl, Peter; Ely, Eugene Wesley; Kudchadkar, Sapna R.; Takahashi, Kunihiko; Elhadi, Muhammed; Gurjar, Mohan; Leong, Be Kim; Chung, Chi Ryang; Balachandran, Jayachandran; et al. (Frontiers in Medicine, 2021)
Background: Data regarding delivery of evidence-based care to critically ill patients in Intensive Care Units (ICU) during the COVID-19 pandemic is crucial but lacking. This study aimed to evaluate the implementation rate of the ABCDEF bundle and ICU diaries for patients without and with COVID-19 infections in ICUs, and to analyze the impact of COVID-19 on implementation of each element of the bundle and independent associated factors. Methods: A world-wide one-day point prevalence study investigated the delivery of the ABCDEF bundle and ICU diary to patients without or with COVID-19 infections on 27 January 2021 via an online questionnaire. Multivariable logistic regression analysis with adjustment for patient demographics evaluated the impact of COVID-19 and identified factors in ICU administrative structures and policies independently associated with delivery. Results: From 54 countries and 135 ICUs, 1229 patients were eligible, and 607 (49%) had COVID-19 infections. Implementation rates were: entire bundle (without COVID-19: 0% and with COVID-19: 1%), Element A (regular pain assessment: 64% and 55%), Element B (both spontaneous awakening and breathing trials: 17% and 10%), Element C (regular sedation assessment: 45% and 61%) Element D (regular delirium assessment: 39% and 35%), Element E (exercise: 22% and 25%), Element F (family engagement/empowerment: 16% and 30%), and ICU diary (17% and 21%). The presence of COVID-19 was not associated with failure to implement individual elements. Independently associated factors for each element in common between the two groups included presence of a specific written protocol, application of a target/goal, and tele-ICU management. A lower income status country and a 3:1 nurse-patient ratio were significantly associated with non-implementation of elements A, C, and D, while a lower income status country was also associated with implementation of element F. Conclusions: Regardless of COVID-19 infection status, implementation rates for the ABCDEF bundle, for each element individually and an ICU diary were extremely low for patients without and with COVID-19 infections during the pandemic. Strategies to facilitate implementation of and adherence to the complete ABCDEF bundle should be optimized and addressed based on unit-specific barriers and facilitators.